Parameters Affecting Single ZnO Nanowire Assembly by Dielectrophoresis - Achilleas Bardakas; Christos Tsamis (Proceedings)
This study aims to examine the dielectrophoretic assembly of single ZnO nanowires, focusing on the effect of electrode geometry, AC frequency and solvent medium on the alignment performance. Experimental results indicate that the electrode geometry significantly affects the capturing performance due to the electric field distribution. Utilizing ethanol as the solvent medium resulted in repeatable nanowire alignment at the optimal AC voltage frequency.